'Good Sport': Different Dimensions and Their Constitutive Properties From the Ontological and Moral Point of View - Mareš Lukáš (Sciendo, 2023)
This paper deals with the question "What is Good Sport?". It aims to enrich previous discussions of the issue by offering a systematic and comprehensive account of good sport, which is missing in the existing literature. The topic is analysed from the ontological and moral point of view. This project builds primarily on moral realism with an emphasis on objective moral values (Spaemann), traditional virtue ethics (Plato, Aristotle) as applied in sport (Pisk, Feezell), and the conceptions of relevant modern philosophers concerned with the ontology of sport (Suits, Fraleigh, Kretchmar, Butcher, Schneider, Jirásek, and others). I maintain that good sport involves various dimensions that need to be distinguished in order to analyse the concept properly. These are good sport as an activity, as an attitude, as an environment (culture), and as fandom. The primary task of this paper is to describe the most relevant properties of good sport in the first three dimensions, indicate their authors/supporters in the tradition of the philosophy of sport, and offer reasons why these properties are constitutive of good sport. I do not aim to analyse each property in detail, but to outline the general framework of good sport. The final classification of properties is analysed in terms of its strengths and weaknesses. I draw mainly from philosophy of sport literature written in English and from key figures in the tradition.